Panama - Poverty Assessment : Toward Effective Poverty Reduction - World Bank (Washington, DC, 2013)
The Poverty Assessment for Panama, Toward Effective Poverty Reduction, focuses on: analyzing poverty, inequality, human development, GDP growth and other social indicators in Panama between 1997 and 2003; providing analytical and advisory support to the Government of Panama aimed at implementing a new strategic vision for poverty reduction; and supporting the country in capacity building in poverty diagnostics and policy evaluation. The report concludes that there is a need to develop a clear social protection strategy with specific targets which should drive the process of resource allocation in the sector. Specific policy recommendations are made in the areas of nutrition programs, education, housing, water and energy subsidies, monitoring mechanisms and institutional arrangements.